CLUSTER ANALYSIS OF THE REGIONS OF THE CENTRAL FEDERAL DISTRICT SOCIO-ECONOMIC AND DEMOGRAPHIC INDICATORS - Irina V. Orlova; Elena S. Filonova (Статистика и экономика)
In the article, the paper classifies the regions of the Central Federal district level indicators of their socio-economic and demographic situation. Defined the typology of the clusters identified problems of the regions and groups of regions on the basis of what identifies key threats to internal development of the Central Federal district.